Perception of medical students on implementation of Clerkship model in Community medicine - Mohsin, Shamaila; Javed, Ayesha; Ajmal, Memoona; Abdur Rauf, Aayesha Bint; Sadiq, Mohammad Awais; Aamir, Ibrahim (Journal of the Pakistan Medical Association, 2026)
Objectives: To explore the learning perspective and experience of fourth year medical students in the clerkship programme, and to identify the key challenges faced by them. Method: The qualitative, phenomenological study was conducted at the Army Medical College, Rawalpindi, Pakistan, from June to September 2024, and comprised fourth year students of either gender who completed their six-week clerkship rotation in Community Medicine within the specified timeframe. Data was collected through in-depth interviews till data saturation was achieved. The interviews were audio-recorded, and transcribed using an artificial intelligence tool. The data was subjected to thematic analysis using the Ritchie and Spencer framework. Results: Of the 15 students, 8(54%) were males and 7(46%) were females. The overall age ranged 21-22 years, and 10(66.6%) had an urban background. Data analysis led to four key themes: innovative learning, including curriculum synergy, scaffolding in learning, and reflective engagement; conduct of clerkship, including pre-visit briefings, instructor-led visits, and theme-based content; personal skill and growth, including cultural familiarity, confidence building, and communication skill enhancement; and structural limitation, including time management, burden of multitasking, and large batch size. While overall satisfaction with the module was high, students highlighted areas of structural limitations. Conclusions: There was a high level of overall satisfaction with the clerkship module, but the students highlighting some structural limitations that need to be addressed to optimise the learning experience. Key Words: Medical education, Medical clerkship, Students’ perception, Clinical, Teaching and learning.